“Sosis Poska” (Sosialisasi Skor Poedji Rochjati Bersama Kader) Di Desa Pandansari Wilayah Kerja Puskesmas Kintap - Rina Rina; Ika Friscila; Nova Harisanti; Selly Morsa Khansa Aulia (Jurnal Pengabdian Bidang Kesehatan, 2024)
Reducing MMR and AKB is a priority for health development as stated in Presidential Regulation Number 18 of 2020 concerning the 2020-2024 National Medium-Term Development Plan. The main causes of maternal death are hypertension in pregnancy and postpartum hemorrhage. This cause can be minimized if the quality of Antenatal Care is carried out properly. Some conditions that can cause the condition of pregnant women are not healthy. High-risk pregnancy is a pregnancy condition that can threaten the health and safety of the mother and fetus. This condition can be caused by complications during pregnancy, but it can also be caused by a medical condition that the mother has had since before pregnancy. The Poedji Rochjati scorecard (KSPR) is a scorecard used as a family-based antenatal screening tool to find risk factors for pregnancy. The challenges faced by cadres in carrying out health development activities are generally caused by the lack of education level and lack of training provided to them regarding their duties as Posyandu cadres. The purpose of the activity "SOSIS POSKA (Socialization of Poedji Rochjati Scores with Cadres) is expected that pregnant women with high risk can be detected as early as possible so that action planning can be carried out and can reduce maternal and infant mortality (AKB). This activity will be carried out in January 2024, carried out in two places, namely the Pandansari village Polindes and at the cadres' house, in the Kintap Health Center Working Area, Tanah Laut Regency, South Kalimantan. Pandansari Village was chosen to be given the innovation of the POSKA SOSIS program because it is a village with 89 pregnant women and most of them have a high risk (pregnant women >35 years, hypertension, pregnant women with comorbidities). The participants of this activity were cadres totaling 15 people. The activities carried out were Socialization about Poedji Rohjati Score, Simulation of Poudji Rochjati Score implementation, Evaluation, and question and answer. In this activity participants gave a fairly good response and discussed with each other, what things can help so that the objectives of this program are understood and can be implemented properly and correctly.